The Influence of Leadership Style and Discipline on Employee Performance at PT. Notojoyo Nusantara Malang - Pamungkas, Faisal Dinar; Agus Purnomo Sidi (Publisher Cv. Inara, 2022)
This study aims to determine how the influence of leadership style and discipline on employee performance at PT. Notojoyo Nusantara in a case study of the construction of the Greenstone City Malang housing area. This study used a research instrument, namely a questionnaire to obtain primary data. The population in this study were all employees of Greenstone City with the determination of the sample using the saturated sample technique with the stratified random sampling method. Respondents in this study were 44 employees. Analysis of the data in this study using multiple linear regression analysis where it is known that leadership style and discipline have no significant positive effect on the performance of Greenstone City employees.